SISTEM PAKAR DIAGNOSA PENYAKIT PADA TANAMAN PADI MENGGUNAKAN METODE FORWARD CHAINING - Edi Wahyu Pratama; Deanna Durbin Hutagalung (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
Application of an expert system for diagnosing diseases in rice plants using the forward chaining method (Case Study: Desa Sribantolo Belitang II) was created to find out the symptoms of rice diseases and solutions for handling rice plants, providing solutions to farmers to deal with rice plant diseases, to implement the forward chaining method in the process of diagnosing existing diseases in rice plants based on predetermined rules. The website-based expert system application for diagnosing rice diseases is designed using the PHP programming language and MySQL database which in the final stage can function to facilitate data processing, for the implementation phase it uses UML (Unified Modeling Language) which can analyze input data and output data. The forward chaining method is a conclusion based on existing facts that leads to that conclusion with the IF part of the IF-THEN rules. To ensure the system runs well, two stages of testing were carried out, namely white box and black box testing in the process of managing symptom data, managing rice disease data and testing showing the results of disease diagnosis reports in rice plants